THE EFFECT OF POSITIVE, NEGATIVE, NEUTRAL MOOD ON ETHICAL AUDITOR JUDGMENTS - Nur'aini Rokhmania (Universitas Hayam Wuruk Perbanas, 2013)
Mood as the factor in decision making is really important to be studied, especially for auditors.Auditors are professional groups that are required to act professionally in any psychologicalconditions. This research attempts to investigate whether the auditors with differentmoods (positive, negative or neutral) will construct ethical judgments with different ethicallevels. It was conducted by distributing questionnaires to the auditors who work at publicaccountant offices (KAP) in Surabaya. The questionnaires are related to two cases associatedwith ethical dilemmas. The first case is related to the decline of inventory values, whilethe second case is concerned with the reporting of the findings of the 25 audit posts. Thequestionnaires are sent through two stages: by email addresses of KAP in Surabaya and bysending files directly to the KAP. The total respondents are 65 auditors. The results showthat 1) positive mood auditors make ethical judgments with the different ethical level compareto negative mood auditors 2) neutral mood auditors make ethical judgments with thedifferent ethical level compare to negative mood auditors 3) positive mood auditors makeethical judgments with the similar ethical level with neutral mood auditors.